Development of common wheat lines with the recombinant arm 1RS as a source of new combinations of disease and pest resistance genes - Kozub, N.A.; Sozinov, I.A.; Bidnyk, A.Ya.; Demianova, N.A.; Blume, Ya.B.; Sozinov, A.A. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2016)
A combination of recombinant-inbred lines of the F6 generation from the cross B-16 ќ AR 7086 between lines with two wheat-rye translocations, 1BL/1RS from the Petkus and 1AL/1RS from the rye Insave, was developed. Using gliadin and secalin loci as genetic markers we identified recombinant arm 1RS in positions 1A and 1B in about 10% of lines. The rest of lines with the rye material may also carry recombinant 1RS, which can be identified with DNA markers. Lines with recombinant arm 1RS may serve as a source of new combination of rye genes for disease and pest resistance.